At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
ok thanks so much
x=1 and z=3
The is a literal equation with substitution I flipped the 2z = 1 + 5x It was originally 2z - 5x = 1
it doesnt matter:)
divide by 2 to get z alone
I divide what by two?
2z = 1 + 5x -----------; z = (1/2) +(5/2)x 2
What about the first equation?
what about it?
What happens to it
you sub the z value into it and solve for x
7z - 3x = 18 7((1/2)+(5/2)x) - 3x = 18
Then what do I do?
7((1/2)+(5/2)x) - 3x = 18 (2) 7(1+5x) - 6x = 36
7+35x -6x = 36 x = 1
Ugh. Now I should have known that!
i goofed that answer but you see it lol
What about the 7?
Doesn't it get multiplied by 2 also?
7+35x -6x = 36 29x = 29 ..... x=1; lol thats a coincidents
lets focus on that part and see what I did ok?
1+5x 7( ----- ) times 2 = 7(1+5x) 2
How do I find the Y again?
Because I am confused about that bit right know?
the y or the z?
ok... do you see why when we mulitply by 2 we get 7(1+5x) tho?
then lets solve for x: 7+35x -6x = 36 ; -7 and add like terms 7-7+35x -6x = 36-7 29x = 29 x = 1 right?
Yes I have the much of the problem solved :D
2z = 1 + 5x 2z = 1+5 2z = 6 z = 3
Finally the problem is finished :D
once you know what x is....use it lol
The problem looks like this 7z - 3x = 18 2z - 5x = 1 changes to 2z = 1 + 5x Then I divide 2z by 2 to get 7z - 3x = 18 z = 1/2 5x/2 which turns to 7(1/2) 5x/2) - 3x = 18 which turns to 7 + 35x -6x = 36 which turns to 7 + 29x = 36 which turns to 29x = 29 then x = 1 then 2z = 1 + 5 (1) 2z = 1 + 5 2z = 6 z = 3 (1,3)